Antioxidant, physicochemical and microbiological characteristics of fermented and unfermented drink of three varieties of dragon fruits (Hylocereus spp) - Ochoa-Velasco, Carlos Enrique (2012)
Dragon fruit juice from three variety (red, pink, and white) were evaluated in pH, total soluble solids, titratable acidity, color, phenolic compounds, antioxidant capacity, while in fermented dragon fruit juice with Saccharomyces cerevisiae were also evaluated the mesophylls and yeasts plus molds, and alcohol grade. The contents of total soluble solids and pH decreased in the fermented juice of all varieties as consequence of the fermentation process. The phenolic compounds were higher in the red dragon fruit juice, followed by the pink and white dragon fruit with average values of 45.3, 32.1 y 24.6 mg of Gallic acid/100 mL of juice, respectively. Therefore, the antioxidant activity was higher in the red dragon fruit juice (160.84 mg of Trolox/100 mL of juice). Fermenting the juice increased the phenolic compounds (changing of 45.31 to 51.38 mg of galic acid/100 mL of juice, in red dragon fruit), however decreased the antioxidant activity (124.51 to 82.96 mg of Trolox/100 mL of juice, in pink dragon fruit). The alcohol grades in the fermented juices were among 2.9 to 3.9 % (v/v). At the end of the fermentation the higher yeasts plus molds (1580 CFU/mL) were in the white dragon fruit juice. However, after the pasteurization process the microbial load in all treatments were lower to 10 CFU/mL. The development of products such as fermented juice is a viable alternative for the commercialization of products derived from dragon fruit.